2019
DOI: 10.1371/journal.pone.0220576
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic noise affects male house wren response to but not detection of territorial intruders

Abstract: Anthropogenic noise decreases signal active space, or the area over which male bird song can be detected in the environment. For territorial males, noise may make it more difficult to detect and assess territorial challenges, which in turn may increase defense costs and influence whether males maintain territory ownership. We tested the hypothesis that noise affects the ability of male house wrens ( Troglodytes aedon ) near active nests to detect intruders and alters responses to them. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 56 publications
0
25
2
Order By: Relevance
“…Units were pre‐programmed to begin recording 1 hr before to 4 hr after sunrise (Eastern Standard Time, EST) in 30‐min recording increments. Playbacks took place between sunrise and 1100 (EST) on days with minimal wind speed and no precipitation and followed the same procedure used by Grabarczyk and Gill (2019a). Briefly, we created 28 playbacks from recordings of male house wrens breeding in southwest Michigan during 2015–2016.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Units were pre‐programmed to begin recording 1 hr before to 4 hr after sunrise (Eastern Standard Time, EST) in 30‐min recording increments. Playbacks took place between sunrise and 1100 (EST) on days with minimal wind speed and no precipitation and followed the same procedure used by Grabarczyk and Gill (2019a). Briefly, we created 28 playbacks from recordings of male house wrens breeding in southwest Michigan during 2015–2016.…”
Section: Methodsmentioning
confidence: 99%
“…Males sing with eventual variety, repeating the same terminal section several times before gradually transitioning to a new song type (Kroodsma, 1977; Rendall & Kaluthota, 2013). Therefore, to mimic natural singing patterns, a single song type was repeated every 15 s for 10 min, similar to typical rates of singing (Grabarczyk & Gill, 2019a). From the collection of 28 exemplars used in Grabarczyk & Gill, 2019a, 16 were randomly selected for use in the present study (two playbacks were used twice, one in 2016 and one in 2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fewer studies have investigated the perception and response behaviours of target receivers to songs from different noise‐habitats (Mockford and Marshall , Ripmeester et al , Luther and Magnotti , LaZerte et al ). However, recent work has shown that while birds do not necessarily respond less strongly to songs in elevated noise‐habitats (Phillips and Derryberry , Grabarczyk and Gill ) they often respond less strongly to songs from habitats with noise levels that differ from their own habitat (Mockford and Marshall , Luther and Derryberry ).…”
Section: Introductionmentioning
confidence: 99%